2008
DOI: 10.1128/aem.01087-08
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella enterica Serovar Enteritidis Genes Induced during Oviduct Colonization and Egg Contamination in Laying Hens

Abstract: Salmonella enterica serovar Enteritidis is the predominant serovar associated with salmonellosis worldwide, which is in part due to its ability to contaminate the internal contents of the hen's egg. It has been shown that S. enterica serovar Enteritidis has an unusual tropism for the avian reproductive tract and an ability to persist in the oviduct and ovary. Factors allowing S. enterica serovar Enteritidis strains to contaminate eggs could be a specific interaction with the oviduct tissue, leading to persisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 63 publications
3
70
0
2
Order By: Relevance
“…Van Immerseel et al, using avian intestinal and cecal epithelial cell lines, also observed increases in invasion of S. Enteritidis exposed to acetate for 4 h and decreases with propionate and butyrate (265,344). Gantois et al reported that exposure of S. Enteritidis and S. Typhimurium to butyrate for 4 h resulted in the lowest percentage of invasion of HeLa cells (345).…”
Section: Salmonella Virulence Response and Organic Acidsmentioning
confidence: 95%
See 1 more Smart Citation
“…Van Immerseel et al, using avian intestinal and cecal epithelial cell lines, also observed increases in invasion of S. Enteritidis exposed to acetate for 4 h and decreases with propionate and butyrate (265,344). Gantois et al reported that exposure of S. Enteritidis and S. Typhimurium to butyrate for 4 h resulted in the lowest percentage of invasion of HeLa cells (345).…”
Section: Salmonella Virulence Response and Organic Acidsmentioning
confidence: 95%
“…Lawhon et al concluded that acetate provided a signal for invasion through the production of cytoplasmic acetyl-phosphate, while propionate and butyrate repressed invasion genes (348). Gantois et al conducted comparative transcriptomic analyses of S. Enteritidis and S. Typhimurium and reported that butyrate downregulated SPI-1 genes, including the regulatory genes hilD and infV, while Huang et al identified formate as a diffusible signal to induce SPI-1 genes and invasion (345,349). Virulence gene responses to organic acids may vary in different serovars as well.…”
Section: Salmonella Virulence Response and Organic Acidsmentioning
confidence: 99%
“…Immunization with purified Type I fimbriae reduces S. Enteritidis contamination of reproductive organs and eggs (De Buck et al 2005) and candidate receptors have been identified in reproductive tract tissue (De Buck et al 2003). A positive regulator of Type I fimbriae expression was also induced in the reproductive tract and in laid eggs (Gantois et al 2008b). A role for curli fimbriae and flagella in growth in eggs has also been reported (Cogan et al 2004), but the role of other surface structures, including T3SSs, in reproductive tract colonization requires further study.…”
Section: Molecular Basis Of Colonization Of the Avian Reproductive Trmentioning
confidence: 99%
“…For instance, Silva et al (84) recently showed that systemic infection of mice by S. Enteritidis requires several genes or genomic islands that are absent from S. Typhimurium and most other Salmonella serotypes. Additionally, a genome-wide screen using in vivo expression technology (IVET) and transposon-mediated mutagenesis has identified several S. Enteritidis genes that contribute to S. Enteritidis tropism to the avian reproductive tract and survival in egg albumen (11,29). Moreover, it has been reported that Salmonella requires different genes in different hosts, suggesting that Salmonella harbors both conserved and host-specific colonization factors (7,9,56,64,80,84), reinforcing the need to study the genetic basis of the pathogenesis of S. Enteritidis, the Salmonella serotype responsible for the largest proportion of food-borne gastroenteritis.…”
mentioning
confidence: 99%